An ultra-sensitive test strip combining with RPA and CRISPR/Cas12a system for the rapid detection of GM crops. (February 2023) - Wang, Jinbin; Wang, Yu; Liu, Hua; Hu, Xiuwen; Zhang, Minghao; Liu, Xiaofeng; Ye, Hailong; Zeng, Haijuan
Abstract: Advanced molecular biotechnology has been developed to provide favorable technical support for genetically modified (GM) crop detection. For sensitive on-site detection, a Cas12a-based immunoassay strip was self-prepared and evaluated in this study. The strip was applied to analyze transgenic screening elements P- CaMV 35S and T- NOS by combination with RPA and Cas12a cleavage reaction. The assay can be completed at 37 °C within 40 min, and the result can be interpreted by the naked eye. For strip analysis, 1 copy/μL of the standard plasmid containing T- NOS and 10 copies/μL of the standard plasmid containing P- CaMV 35S could be detected, and the detection limits of genomic DNA were 10 −4 and 0.01 ng/μL for T- NOS and P- CaMV 35S, respectively. In addition, the response signal of the test strips was stable under the detection limit concentration, which was distinguished from the negative control. Moreover, the strip has good specificity for 16 kinds of transgenic samples and can be applied to random samples in the market. In summary, the proposed Cas12a-based strip showed good detection performance and provided an ultra-sensitive tool for the visual detection of GM crops. Highlights: An ultra-sensitive RPA-Cas12a-based immunoassay strip was self-prepared. The strip was evaluated for visual detection of genetically modified crops. The strip could detect 1–10 copies/μL of standard plasmids containing P- CaMV 35S and T- NOS. The method is fit for sensitive, rapid, and on-site detection.